EFFECTIVITY OF PAPAYA LEAVES (Carica papaya l) AS INHIBITOR OF AEDES AEGYPTI LARVAE - Farid, Adityo Muhamad (Majority, 2015)
Abstract Dengue Haemorrhagic Fever (DHF) is an infectious disease that causes global health problems, including Indonesia. One way to prevent dengue transmission is with controlling the main dengue vector which is Aedes Aegypti. Papaya (Carica papaya L.) can be used as control agents against dengue vector. Papaya contains protease enzymes, such as papain and kimopapain, which helps to kill Aedes Aegypti larvae. Papain is a proteolytic enzyme that breaks down essential proteins needed to maintain the development of Aedes Aegypti larvae. Keywords: aedes aegypti larvae, dengue haemorrhagic fever, protease enzymes, Abstrak Demam Berdarah Dengue merupakan penyakit menular yang masih menjadi masalah kesehatan di dunia, termasuk Indonesia. Cara mencegah penularan demam berdarah dengue adalah dengan memutuskan rantai penularannya yaitu dengan pengendalian vektor utama penular DBD di Indonesia yaitu Aedes Aegypti. Pepaya ( Carica papaya L.) merupakan tanaman yang dapat digunakan sebagai pengendali vektor demam berdarah dengue. Kandungan enzim protease, seperti papain dan kimopapain, yang dimiliki oleh pepaya diduga dapat membunuh larva Aedes aegypti. enzim papain merupakan enzim proteolitik yang akan memecah protein-protein penting yang diperlukan untuk perkembangan larva Aedes aegypti. Kata kunci: larva aedes aegypti , demam berdarah dengue, enzim protease